ASPECTS OF MODERN LINGUISTICS ANTHROPOLOGY IN TOBA BATAK TRADITIONAL WEDDING CEREMONY - Theresia Novena Monalisa Sinaga; Angri Tuti Arta Tampubolon; Ismarini Hutabarat (LPPM Universitas Darma Agung, 2022)
This study focused on the aspects of modern linguistics in Toba Batak traditional wedding ceremony. The problems of the study (1) what aspects of modern linguistics anthropology are found in Toba Batak traditional wedding ceremony? (2) how are the aspects of modern linguistics anthropology interconnected in Toba Batak traditional wedding ceremony?. This study found that (1) there were three aspects of modern linguistics anthropology in Toba Batak traditional wedding ceremony; they were performance, indexicality and participation. (2) The three aspects found in Toba Batak traditional wedding ceremony were inseparable because they were interrelated strongly one another.